Dexamethasone Versus Lidocaine: Evaluation of Their Roles in Reduction of Sore Throat after Endotracheal Extubation Following General Anaesthesia - Islam, Md Saiful; Bhowmick, Lipon Kanti; Khan, Md Mashfiqur Rahman; Mahabubuzzaman, Mohammad; Rahim, Md Abdur; Kabir, Md Humayun; Sheikh, Md Zubyeer Ali (Community Based Medical Journal, 2026)
Postoperative sore throat (POST) is a common complaint in patients requiring general anaesthesia with endotracheal intubation (ETI) for surgery. Many procedural modifications and drugs were tried to reduce such discomfort. This prospective randomized controlled study was conducted in a tertiary care hospital in Dhaka, Bangladesh, between July and December of 2024, to determine the efficacy of dexamethasone and lidocaine in reducing postoperative sore throat in patients receiving general anaesthesia with endotracheal intubation. A total of 150 patients were enrolled and divided into 3 groups in this study with 50 patients in each group. Simple Random sampling technique was used. Group D (dexamethasone) received 5 mg dexamethasone and group L (lidocaine) received 1.5 mg/kg lidocaine 30 minutes before operation. However, group C (control) did not receive any study drug. Data was collected through semi-structured questionnaire in patient data sheet and analyzed. The incidence of POST was found 30%, 38% and 52% in dexamethasone, lidocaine and control groups respectively (p<0.05). Dexamethasone reduced the incidence of POST in the first 24 hours (OR=0.4, 95% CI=0.17–0.9). However, there was no significant difference of severity of POST at 3 hours, 6 hours, 12 hours and 24 hours (p>0.05) after extubation. To conclude, intravenous dexamethasone was found more effective than intravenous lidocaine in reducing the incidence of postoperative sore throat after endotracheal extubation following general anaesthesia. CBMJ 2026 January: vol. 15 no. 01 P:10-16